Effectiveness of Behavior Conservation with Technical Modeling Through Lesson Learning to Increase Fun Characters for Others - Ahmad Imran; Ni Ketut Suarni; I Ketut I Ketut Darsana (International Conference on Technology and Educational Science)
The purpose of this study is to improve the character of pleasing others. -posttest control group design The 32-student self-collected data questionnaire was collected by the self-assurance questionnaire. This is evidenced by the value of the t table, tcount (4.31 > ttable = 1.67022 so that ho is rejected and Ha is accepted so there are significant differences, so it can be concluded that Ivan Pavlov's behavioral counseling with modeling techniques is effective in enhancing the character o f pleasing other students.